A case of stroke as a unique sign of subclinical infective endocarditis by Abiotrophia defectiva: a case report - Silvia Puxeddu; Valeria Virdis; Daniele Sacco; Mario Depau; Alessandro M. Atzei; Lorella Pisano; Marcello Di Rosa; Stefania Vacquer; Giorgio Accardi; Emiliano M. Cirio; Aldo Manzin; Cristiana Marinelli; et al. (International Journal of Emergency Medicine)
Abstract Purpose Here we describe a patient admitted for a stroke that was unexpectedly correlated with subclinical infective endocarditis attributable to a rarely opportunistic pathogen, Abiotrophia defectiva. Case report A 75-year-old man presented with a stroke. Transesophageal echocardiography suggested vegetation on all aortic valve cusps, despite the absence of clinical or laboratory signs of infection. Surprisingly, three sets of blood cultures collected without fever were positive for A. defectiva. Although the patient did not exhibit classic signs of infection during hospitalization, the severity of the valve condition necessitated replacement with a bioprosthesis. Conclusions This clinical case underscores the importance of investigating the infective origin of endocarditis, even in the absence of clinical or laboratory evidence. Physicians should maintain a high level of suspicion, especially in patients with highly suggestive anamnestic characteristics.